Synthesis revolution (Nat Ecol Evol, 2020)
Evidence synthesis facilitates a more robust understanding of generalities in ecology and evolution, as well as the effectiveness of conservation interventions. However, as synthesis methods become embedded in research workflows, it is imperative that the next generation of researchers receives sufficient training.